Pengaruh Model Discovery Learning Berbantuan Media Audio Visual dalam Setting Lesson Study Terhadap Hasil Belajar IPA Mahasiswa PGSD Undiksha UPP Denpasar Tahun 2017 - I Ketut Ardana (Universitas Pendidikan Ganesha, 2018)
This research was conducted to determine the significant diversification in science’s learning outcome that are learned by using discovery learning model of audio-visual media in lesson study setting and it was learned using conventional learning on PGSD’s student at Undiksha UPP Denpasar in 2017. This research is a quasi-experimental research with nonequivalent control group design. Population in this research is all student of PGSD amounted 182 students from 4 classes. The sample is determined by using random sampling technique, so that the sample of J class of 45 students and H class of 46 students was obtained. The data of science’s learning outcomes were collected using the usual double choice objective test, then analyzed by t-test. The result of this study showed the average experimental group value is 84.19 while the control group average is 70.00. Thus it can be concluded that there are significant differences in learning outcomes of science that are learned by using discovery learning model of audio-visual media in lesson study setting and learning using conventional learning in PGSD’s student at Undiksha UPP Denpasar in 2017.